Problematika sledování environmentálních nákladů ve veřejné správě - Pechová, Iveta (Univerzita Pardubice, 2006)
Práce se zabývá teoretickými problémy sledování environmentálních nákladů ve veřejné správě. Je zpracována rešerže literárních pramenů z České republiky a zahraničí. Také je vypracována případová studie obce v ČR.

The project deals with theoretic problems of environmental costs monitoring in public administration. The search of literary sources from the Czech republic and foreign countries is made in this project. There is a study about one municipality in the Czech republic.
Problems of environmental costs monitoring in public administration
Keywords: environmental costs; Public Administration; environmental investment; National environmental fund; environmentální náklady; environmentální investice; Státní fond životního prostředí; veřejná správa